Successful marketing strategies for nonprofit organizations winning in the age of the elusive donor - McLeish, Barry, 1956- (Wiley, 2011)
"From a leading expert on nonprofit marketing, the only marketing handbook a nonprofit manager will ever need-now fully revised and updated In Successful Marketing Strategies for Nonprofit Organizations, Second Edition, nonprofit marketing guru Barry J. McLeish shares everything he's learned during more than two decades managing and consulting nonprofits of every shape and size. Skipping all the arcane theory and the business school jargon, he gives you clear, step-by-step advice and guidance and all the tools you need to develop and implement a sophisticated marketing program tailored to your organization's needs and goals. New sections on the new media available to nonprofit marketers. Techniques for analyzing your market and developing a comprehensive marketing plan. Marketing strategies that will support fund-raising, promote new services, and enhance your organization's reputation and visibility. Methods for developing a marketing program that reaches both the consumers of your service and the donors who support your organization. Do you need to breathe new life into your existing marketing department? Successful Marketing Strategies for Nonprofit Organizations, Second Edition gives you the tools, the know-how, and the confidence you need to succeed."--